E-swim - Enterprise Semantic Web Implementation Model: Towards a systematic approach to implement the Semantic Web in Enterprises - Ferreira, Reinaldo (2016)
The adoption of Semantic Web technologies constitutes a promising approach to data structuring and integration, both for public and private usage. While these technologies have been around for some time, their adoption is behind overall expectations, particularly in the case of Enterprises. This paper discusses the challenges faced in implementing Semantic Web technologies in Enterprises and proposes an Implementation Model that measures and facilitates that implementation. The advantages of using the model proposed are two-fold: the model serves as a guide for driving the implementation of the Semantic Web as well as it helps to evaluate the impact of the introduction of the technology.